RENAL ARTERIES REMODELLING — THE INITIATOR AND TARGET OF CARDIORENAL CONTINUUM - T. S. Levitskaya; М. М. Batyushin; D. G. Pasechnik; E. G. Asrumian (Кардиоваскулярная терапия и профилактика)
Cardiorenal syndrome (CRS) is one of the most important problems in contemporary medicine, due to high values of morbidity and mortality from cardiovascular and renal systems. Hence the presence of CRS significantly potentiates the risk of heart and kidney disease progression. The most important step of CRS is tissues and organs remodeling that leads to irreversibility of changes. At the date the problem of renal tissue changes is well known and covered in relevance to the malfunctioning, for patients with cardiovascular pathology. The role of renal arteries and their first level significance in development and progression of cardiovascular diseases remains under discussed. The article provides the main data on renal arteries remodeling and their place at the initiation and progression of CRS, as demonstrating a very high significance of the function and structure assessment for risk of the most socially important cardiovascular diseases.